Influence of weight and type of planting material on fruit quality and its heterogeneity in pineapple [Ananas comosus (L.) Merrill] - Fassinou Hotegni, V. Nicodème; Lommen, Willemien J. M.; Agbossou, Euloge K.; Struik, Paul C. (Frontiers in Plant Science, 2015)
Cultural practices can affect the quality of pineapple fruits and its variation. The objectives of this study were to investigate (a) effects of weight class and type of planting material on fruit quality, heterogeneity in quality and proportion and yield of fruits meeting European export standards, and (b) the improvement in quality, proportion and yield of fruits meeting export standards when flowering was induced at optimum time. Experiments were conducted in Benin with cvs Sugarloaf (a Perola type) and Smooth Cayenne. In cv. Sugarloaf, experimental factors were weight class of planting material (light, mixed, heavy) and time of flowering induction (farmers’, optimum) (Experiment 1). In cv. Smooth Cayenne an additional experimental factor was the type of planting material (hapas, ground suckers, a mixture of the two) (Experiment 2). Fruits from heavy planting material had higher infructescence and fruit weights, longer infructescences, shorter crowns and smaller crown: infructescence length than fruits from light planting material. The type of planting material in Experiment 2 did not significantly affect fruit quality except crown length: fruits from hapas had shorter crowns than those from ground suckers. Crops from heavy planting material had a higher proportion and yield of fruits meeting export standards than those from other weight classes in Experiment 1 only; also the type of planting material in Experiment 2 did not affect these variates. Heterogeneity in fruit quality was usually not reduced by selecting only light or heavy planting material instead of mixing weights; incidentally the coefficient of variation was significantly reduced in fruits from heavy slips only. Heterogeneity was also not reduced by not mixing hapas and ground suckers. Flowering induction at optimum time increased the proportion and yield of fruits meeting export standards in fruits from light and mixed slip weights and in those from the mixture of heavy hapas plus ground suckers.